Development of Student Worksheet Integrated Scientific Literacy for The Using Of Physics Practicum Kit in Simple Harmonic Vibration - Aivani Caesaria; Hidayati Hidayati; Fatni Mufit; Silvi Yulia Sari (Physics Learning and Education, 2023)
Facts found in the field found that the available Practical KIT is complete, but teaching materials in the form of the student worksheet are still built from Practical KIT and are still general in nature. One of the solutions to overcome these problems is the development of worksheets integrated with scientific literacy for the use of KIT Physics Practicum on Simple Harmonic Vibration Material. The purpose of this study was to determine the feasibility of the validity of the student worksheet Integrated with Scientific Literacy The research conducted included a type of research and development with the ADDIE model which consists of 5 stages, namely, Analysis, Design, Development, Implementation, and Evaluation. This research was conducted up to the Development stage where each stage was carried out Evaluation Research is limited to the Development stage at the validity test stage. The object of research is student worksheet integrated with science literacy. Data sources were obtained from the results of expert validation by Physics lecturers of Faculty of Mathematics and Natural Sciences, Padang State University Padang State University. The data collection instrument in this study was a validity test sheet. Data analysis techniques for instrument and product validation using V Aiken. The results of this study obtained three results, namely first based on preliminary analysis obtained the problem of practicum KIT available has not been maximally utilized so it is necessary to develop student worksheet Integrated Scientific Literacy. Secondly, at the design stage, the student worksheet integrated with scientific literacy has been designed. Third, the validity test results obtained an average of 0.86 with a very valid category. From this study it can be concluded that the development of student worksheet Integrated with Scientific Literacy for the Use of Physics Practicum KIT on Simple Harmonic Vibration Material is feasible to use in physics learning.